Evaluation of Congenital Syphilis cases at the maternity of the Hospital da Sociedade Portuguesa de Beneficência de Campos, RJ - Fernandes, Regina Célia SC; Fernandes, Paulo GCC; Nakata, Talita Y (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: congenital syphilis remains an important challenge to public health despite the availability of diagnosis and treatment. Objective: studying the diagnostic evaluation and the treatment of maternal syphilis as well as their newborns at the Maternity of the Hospital da Sociedade Portuguesa de Beneficência de Campos, RJ. Methods: revision of clinical records and interviews with pregnant women presenting positive VDRL at delivery or submitted to curettage; revision of clinical records of their newborns, from August 2006 to April 2007. Results: the prevalence of positive VDRL among pregnant women was 1.18% (26/2117). Only 8% (2/25) of positive VDRL pregnant women were identified at first trimester. In 28% (7/25) pregnants were correctly treated and treatment was not performed in 40% of the cases (10/25). Only 12% (3/25) of their partners were treated. Newborns were free of symptoms in 80% (16/25) of cases. Bone involvement was present in 10% (2/25) of newborns and positive VDRL in cerebrospinal fluid reached 35% (7/25). All babies were correctly investigated and treated. Conclusion: there was an expressive reduction in prevalence of positive VDRL among pregnant women for the period of study as compared with data from 2001 and 2003. The challenge of precocious identification and correct treatment of pregnant women still remains, as well as their partners, fundamental aspects for disease control.